The influence of triadimenol on banana cultivars Basrai and Williams under in vitro culture - Galal, A.A., A.A.; Ibrahiem, A.I., A.I.; Jehan M.M. Salem, (Penerbit Universiti Kebangsaan Malaysia, 2012)
Triadimenol is a systemic fungicide with protective, curative and eradicant action. It is highly effective in controlling a variety of economically important pathogenic fungal caused diseases on plant. This study was conducted to investigate the influence of triadimenol on in vitro culture of banana cultivars Basrai and Williams. The effects of systemic triadimenol were tested on the shoot-tip explants. Explants were cultured on Murashige and Skoog (MS) basal solid medium supplemented with 5 mg/l 6-benzylaminopurine (BAP) or 1 mg/l indole-3-butyric acid (IBA) and different concentration of triadimenol. Results showed the viability of both banana cultivars were decreased as well as triadimenol concentration increased. Most of shoot-tip explants died at the lethal concentration (60 mg/l) of triadimenol. The shoot-tip proliferation, the number and length of lateral buds and efficiency of root system formation were decreased as the triadimenol concentrations increased. The sub-lethal concentration (50 mg/l) of triadimenol affected the photosynthetic pigments such as ChI a, ChI b and carotenoids contents and a variation in the number and stain intensity of the polypeptides compared with control ones was exhibited. Triadimenol (50 mg/l) treated shoots also showed dramatic decreasing in the Δ5 sterols; sitosterol, stigmasterol and campesterol content. This study demonstrated that triazole fungicide triadimenol has a similar inhibitory effect on the growth and development of the two banana cultivars Basrai and Williams.